2017
DOI: 10.1128/jvi.01141-17
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Genome Sequencing Reveals Varicella-Zoster Virus Open Reading Frame 12 Deletion

Abstract: The neurotropic herpesvirus varicella-zoster virus (VZV) establishes a lifelong latent infection in humans following primary infection. The low abundance of VZV nucleic acids in human neurons has hindered an understanding of the mechanisms that regulate viral gene transcription during latency. To overcome this critical barrier, we optimized a targeted capture protocol to enrich VZV DNA and cDNA prior to whole-genome/transcriptome sequence analysis. Since the VZV genome is remarkably stable, it was surprising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Until now, the VZV transcriptome have been analyzed by Northern blot, primer extension, microarray and Illumina sequencing [17,[68][69][70][71][72][73][74][75]. These techniques have generated useful data, but they have limitations to provide a comprehensive list of the VZV transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the VZV transcriptome have been analyzed by Northern blot, primer extension, microarray and Illumina sequencing [17,[68][69][70][71][72][73][74][75]. These techniques have generated useful data, but they have limitations to provide a comprehensive list of the VZV transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the beta and gammaherpesviruses, splicing events are rare among the alphaherpesviruses [21,22]. In VZV only a few genes have been shown to produce spliced mRNAs so far, which include the ORF0 (also referred as ORFS/L) located at the termini of UL region, the UL15 homologue ORF42/45, the glycoprotein M (gM) encoding ORF50, and the newly discovered, multiple spliced VLT [6,9,23,74,75].RNA editing includes the adenosine deaminase acting on RNA1 (ADAR1) enzyme that catalyzes the C-6 deamination of adenine (A) to inosine (I). The I is recognized as guanine (G) by the reverse transcriptase (RT) enzyme [26], therefore it can be detected with cDNA sequencing methods.…”
mentioning
confidence: 99%
“…Later on, VZV reactivation from dorsal nerve ganglia causes antegrade travel of the virus to cause the dermatomal disease of HZ [89][90][91]. VZV establishes latency in multiple cranial and dorsal root ganglia as well as thoracic sympathetic and enteric ganglia [90,92]. VZV-infected lymphocytes are used to induce latent infection in sensory and enteric neurons.…”
Section: New Data On the Pathogenesis Of Vzv Infectionsmentioning
confidence: 99%
“…Genome-wide mutagenesis has revealed that ORF 7 is a novel VZV skin-tropic factor which is essential for viral replication [339]. Application of enrichment protocols to targeted genome sequencing has revealed the unexpected deletion of a signi icant proportion of VZV-ORF 12 following propagation in culture human ibroblast cells [340]. ORF 25 gene product is an essential hub for protein interactions and is essential for VZV replication [341].…”
Section: Vzv Proteins Cell Components and Cellular Processesmentioning
confidence: 99%
“…Culture adaptation of human herpesvirus 6A/B results in large tandem repeats in the origin of replication and other regions that are not found in low-passage clinical isolates and likely help accelerate viral replication in vitro (1618). Similarly, laboratory passage of human cytomegalovirus, Epstein-Barr virus, and varicella-zoster virus can result in surprisingly large deletions comprising multiple genes and kilobases (1922).…”
Section: Introductionmentioning
confidence: 99%